Teknik Literasi Silang Dalam Model Problem Based Learning: Alternatif Pembelajaran di Masa Pandemi Covid19 - Cholifah Tur Rosidah (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The Covid-19 pandemic has an impact on all lines of life, one of which is the education aspect. The government's policy to implement online lectures has made the lecture process, which was originally face-to-face, also blended learning turned into a full online lecture. This is the basis for researchers to find alternative learning techniques that can be applied in the full online lecture process. In addition, it is also to describe the level of activeness of students in lecturing activities. This study uses a qualitative approach to describe the application of cross-literacy techniques in the problem-based learning model and the students' responses to the implementation of cross-literacy techniques in the problem-based learning model in Indonesian language learning subjects. The research was conducted at the PGSD Study Program at Adi Buana University. Precisely for the 4th semester students taking Indonesian language learning courses in class A. The data was collected using a non-test technique using a list of interview questions, questionnaires and observation sheets. The response to the implementation of the application of the cross literacy technique in the problem-based learning model showed that 89% of students felt that the application of the technique was interesting, made lectures less boring and it became easier to understand the material. Strongly agree with the application of cross literacy techniques in the problem based learning model. The remaining 11% responded in agreement with the application of the technique.